Introduction to graphic design a guide to thinking, process & style - Sherin, Aaris (Bloomsbury Visual Arts, 2018)
"The Graphic Design Style Manual is a clear and engaging introduction for students who are just starting out in their studies. The concepts and terminology as well as the basic purpose of graphic design can be challenging and confusing. The goal of this book is to demystify these concepts with clear and straightforward information, answers to common problems and down-to-earth advice. Each chapter starts with a list of key terms and concepts to provide an easy reference so students can start to produce competent design work more quickly. The Graphic Design Style Manual highlights step-by-step methods for achieving clarity, visual impact and techniques for developing original visual solutions"--Provided by publisher.